Diseño de una Planta Piloto para Extracción de Metabolitos Naturales (Antioxidantes) a Partir de Tomate Chonto - Ocampo Trujillo, Cristian Antonio
This work carried out a comparison from the theoretical review (state of the art) and a simulation in the program super pro designer, of two methods for the extraction of metabolites for the design of a pilot plant. The compared methods were the extraction with organic solvents and the extraction for supercritical fluids since they are applied to this type of extractions. According to the state of the art found by both methods, it was decided to take as a model the method of extraction by supercritical fluids with CO2 for the extraction of lycopene of "chonto" tomato in   view of the advantages in the process with regard to the method of extraction with orgnanic solvents. Theoretically, it is suggested extractions of 85 % to 95 % of purity which is an input data for the simulation by means of the program carried out in the present work. According to the simulations carried out by both methods treated, times of extraction used were 180 to 360 minutes. With the method of supercritical fluids, time can diminish near to 180 minutes since it is observed that it reduces drastically the quantity of extracted substance. When it is defined the method of extraction of the lycopene, it fullfilled the analysis of factors that determined the criteria for the design of the pilot plant, including the costs , planes, the lines of production.